2016
DOI: 10.1007/s10903-016-0539-3
|View full text |Cite
|
Sign up to set email alerts
|

Home Environmental Influences on Childhood Obesity in the Latino Population: A Decade Review of Literature

Abstract: Background Latinos are the largest and fastest-growing ethnically diverse group in the United States. Latino children are also among the most overweight and obese ethnic groups of children in the United States. Research over the last decade has identified the home environment as a key influence on the diet and physical activity of children. Objective To summarize cross-sectional and longitudinal research that has identified factors within the home environment of Latino families that are associated with child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
88
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 45 publications
10
88
1
2
Order By: Relevance
“…This is consistent with previous qualitative research, including our own, and indicates the importance of the family within Latino communities [28,30,50,51]. It also suggests that the family should be considered the unit of change and that interventions focusing on promoting healthy ST will likely be more successful if they consider the entire family unit, including adults (e.g., both parents, other relatives such as grandmothers) and children (younger and older children).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This is consistent with previous qualitative research, including our own, and indicates the importance of the family within Latino communities [28,30,50,51]. It also suggests that the family should be considered the unit of change and that interventions focusing on promoting healthy ST will likely be more successful if they consider the entire family unit, including adults (e.g., both parents, other relatives such as grandmothers) and children (younger and older children).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, parents' own ST was seen as influencing their young children's ST. Results of the current study are similar to that of previous research that indicate an association between home social and physical environment and development of children's early behaviors including ST [11,26,30,33,41,65,66]. This finding suggests that family-centered interventions should address not only children's, but also parents', siblings' and other family members' ST and incorporate parental role modeling of healthy ST behaviors.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A recent review of the literature exploring home environmental influences on childhood obesity in the Latino population concluded that parental influences (e.g., parent feeding practices, modeling), screen time, and physical activity/sedentary behavior, were among those key factors that may contribute to the disproportionate burden of obesity experienced by Latino children (40). The described study, ANDALE Pittsburgh, targets those key factors through a culturally-tailored, home-based child obesity prevention intervention.…”
Section: Discussionmentioning
confidence: 99%